Answer:
As the value of x increases, the value of f(x) will eventually exceed the value of g(x) is the correct option.
Explanation:
A function, f, passes through the points (1,1), (2,7) and (3,25).
The equation of the function 'f' can be written as:
The f(x) is obtained by:
![f\left(x\right)=3f\left(x-1_\right)+4](https://img.qammunity.org/2021/formulas/mathematics/middle-school/z5mxsewnfuqskvnha69cb3c1d8w7sefd6v.png)
![f\left(4\right)=3f\left(3\right)+4=\left(25* 3\right)+4=75+4=79](https://img.qammunity.org/2021/formulas/mathematics/middle-school/h8nz00i4dbgdnsfgaxmioctzvmh3b20jn5.png)
A function, g, passes through the points (1,36), (2,43) and (3,50).
The g(x) is obtained by:
![g\left(x\right)=g\left(x-1\right)+7](https://img.qammunity.org/2021/formulas/mathematics/middle-school/gze714si6ieeyt4wodgql3tbzbcf3u115z.png)
![g\left(4\right)=g\left(4-1\right)+7=g\left(3\right)+7=50+7=57](https://img.qammunity.org/2021/formulas/mathematics/middle-school/jfjn0rt6g27j92t6h3jgivlnevx3blwvm0.png)
So, value of f(x) at x = 4 exceeds the value of g(x) at x = 4.
Therefore, as the value of x increases, the value of f(x) will eventually exceed the value of g(x) is the correct option.